Big patents, small secrets: how firms protect inventions when R&D outcome is heterogeneous - Malte Mosel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
Patents have long been regarded as the 'gold standard' of intellectual property protection. In 'Little patents and big secrets: managing intellectual property', Anton and Yao (2004) call this traditional view into question by finding that firms keep their most important innovations secret. This model modifies key assumptions made by Anton and Yao by accounting for patenting costs, patentability standards, and the fact that patents provide protection in competitive situations where secrecy fails. The latter aspect counteracts the empirically substantiated fact that, in situations where both appropriation mechanisms are applicable, secrecy provides more protection. It is found that firms keep small inventions secret, use both mechanisms for medium inventions, and patent their most important innovations. This result reestablishes the traditional view that patents are crucial to provide R&D incentives and is yet consistent with main empirical findings on the issue.
Keywords: K11; L16; L50; O32; O34; 330; Heterogeneous inventions; innovation size; intellectual property rights; patents; patent filing fees; patentability standards; renewal fees; secrecy; technology evolution; Erfindung; Innovation; Imitationswettbewerb; Patent; Geschäftsgeheimnis; Industrielle Forschung; Patentrecht; Theorie